Brightness perception of white LED lights with different correlated colour temperatures. Issue 4 (July 2015) - Kim, In-Tae; Jang, In-Hyun; Choi, An-Seop; Sung, Minki
Various luminous environments can be created by utilizing light emitting diode (LED) lights which can be easily controlled with diverse illuminance and correlated colour temperature (CCT) levels. Implementation of such luminous environments could affect occupants' perceptions. This study aim to identify subjective brightness perception of young healthy female and male students being exposed to different CCT conditions of LED lights in lecture room environment. To measure brightness perception, three subjective evaluations were conducted. First, brightness perception in different CCTs was compared under single CCT LED lights. Second, a single CCT of LED light was compared to the same CCT under mixed CCTs. Third, different mixing methods for a particular CCT were applied to mixed CCTs of LED lights. The results of the first test showed that the subjects perceived the environmental space to be brighter when exposed to a higher CCT with the same illuminance level. The second experiment showed that LED lights with mixed CCTs are relatively superior to LED lights with a single CCT in terms of brightness perception under the same illuminance level. The third experiment illustrated that the subjects would feel their environment as brighter when exposed to higher CCT and/or with a larger proportion of high CCT. The selections and mixing among different CCTs for classroom design can be determined based on the results of this study where brightness perception is important.